Development Of An Efficient Protocol For The Production Of Phalaenopsis Hybrid Orchid Plantlets - Rajasegar, Arulvilee (2022)
As a monopodial plant, Phalaenopsis is traditionally propagated by off-shoot cutting or division. However, this resulted in a low multiplication rate and hinders the growth of the mother plant and therefore inefficient for large-scale production. Micropropagation has provided a valuable alternative method for the large-scale production of identical orchid plantlets within a short period. The study aimed to improve the proliferation of protocorm-like bodies (PLBs) of Phalaenopsis Fuller’s Light × Phalaenopsis Purple Heart through the micropropagation method. The thin cell layer culture (TCL) approach generated a 2.16 times higher neo-PLB formation rate than the conventional half-PLB explants. The medium composition of full MS medium supplemented with 3% sucrose, 2% banana extract, and 15% coconutwater significantly produced the highest PLB fresh weight (2.499 g) after 4 weeks of culture. The Phalaenopsis PLBs further developed into shoot and root using 1.0 mg/L BAP and NAA mg/L. The incorporation of 1.5 mg/L of glutamine resulted shoot formation with 70% while 1.5 mg/L of arginine increased root formation by 87%, wherein the cultures were differentiated into complete plantlets.